A survey on design and implementation of protected searchable data in the cloud - Dowsley, Rafael; Michalas, Antonis; Nagel, Matthias; Paladi, Nicolae (Computer science review, 2017)
While cloud computing has exploded in popularity in recent years thanks to the potential efficiency and cost savings of outsourcing the storage and management of data and applications, a number of vulnerabilities that led to multiple attacks have deterred many potential users. As a result, experts in the field argued that new mechanisms are needed in order to create trusted and secure cloud services. Such mechanisms would eradicate the suspicion of users towards cloud computing by providing the necessary security guarantees. Searchable Encryption is among the most promising solutions—one that has the potential to help offer truly secure and privacy-preserving cloud services. We start this paper by surveying the most important searchable encryption schemes and their relevance to cloud computing. In light of this analysis we demonstrate the inefficiencies of the existing schemes and expand our analysis by discussing certain confidentiality and privacy issues. Further, we examine how to integrate such a scheme with a popular cloud platform. Finally, we have chosen – based on the findings of our analysis – an existing scheme and implemented it to review its practical maturity for deployment in real systems. The survey of the field, together with the analysis and with the extensive experimental results provides a comprehensive review of the theoretical and practical aspects of searchable encryption.